Analysis of Factors Affecting Teacher Performance at State Elementary School In Rangsang Pesisir District Riau Province - Sarifah Sarifah; Sudarno Sudarno; Sri Listyarini (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2022)
The objective was to determine the factors that influence the high and low performance of teachers in state elementary school in rangsang pesisir district. this research uses percentage analysis method and quantitative and qualitative descriptive statistics. the result is that the factors of organizational commitment, organizational culture, work motivation, leadership style, job satisfaction and work environment are very influential on the performance of teachers furthermore, when viewed from the aspect of factors specifically, the specific factors of these general factors can affect the work results and performance of civic servant teachers in state elementary school with a very influential category